Territorial complexity in fishermen's coves of Chiloé (Chile): Contributions for coastal management - Ther-Ríos, Francisco; Salinas-Vilches, Paula; Gajardo-Gálvez, Gonzalo; Bugueño, Zamir; Gajardo-Cortés, Claudio; Ceballos-Cardona, Mauricio; Valderrama-Bravo, Jaime; Cursach, Jaime; Hidalgo-Garrido, Carlos (Universidad Católica del Norte, Instituto de Investigaciones Arqueológicas y Museo, 2020)
Coastal artisanal fishing communities (small scale coves or “caletas”) are complex socio-ecological systems that adapt to perturbations depending on their inherent complexity and properties. The ability to evaluate and monitor such adaptive response provides information on caletas sustainability, required for reliable territorial and strategic planning. Six caletas from different geographic locations in Chiloe Island, southern Chile, served as a model to identify territorial complexity. This article identified 4 criteria and 16 sub-criteria (using Expert Choice software) as suitable descriptors of their complexity, and hierarchically ranked them according to importance (%). All these variables were merged into a Territorial Complexity Index (ICT), a quali-quantitative estimator of caletas sustainability. A principal Component Analysis, including all sub-criteria, further characterized caletas complexity. This article showed that complexity needs an integrated analysis of the relevant variables to monitor evolutionary trajectories of caletas, and thus ICT is highlighted as a convenient quantitative tool for territorial and strategic planning.